2006
DOI: 10.1590/s1519-69842006000300020
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous growth fingerlings of the Nile tilapia Oreochromis niloticus: effects of density and initial size variability

Abstract: In this study, the effect of initial heterogeneity of weight and density on heterogeneous growth (HetG) evaluated by the coefficient of the variation of weight in the young Nile tilapia Oreochromis niloticus of the territorial species was tested. Fish were maintained in a glass aquarium (8 and 2 L of water) with two levels of initial heterogeneity of weight: low and high, under two density conditions: low and high, thus constituting four conditions (six replications for each). Initially, the weights of the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
(8 reference statements)
1
12
1
1
Order By: Relevance
“…Several authors have reported that crowding intensifies the heterogeneous fish growth, due to the competition for a sparse supply of adequate food or social dominance, which often coincides with increasing fish densities (Sahoo et al, 2004;Jha & Barat, 2005;Barbosa et al, 2006). When growth is density dependent, partial harvest of the standing fish have been use to decrease competition, and thereby increasing individual growth rate.…”
Section: Effect Of Density On Fish Growth and Survivalmentioning
confidence: 99%
“…Several authors have reported that crowding intensifies the heterogeneous fish growth, due to the competition for a sparse supply of adequate food or social dominance, which often coincides with increasing fish densities (Sahoo et al, 2004;Jha & Barat, 2005;Barbosa et al, 2006). When growth is density dependent, partial harvest of the standing fish have been use to decrease competition, and thereby increasing individual growth rate.…”
Section: Effect Of Density On Fish Growth and Survivalmentioning
confidence: 99%
“…However, competition and negative social interaction can decrease after some time and a stage of growth stabilization can then follow. This is due to the appearance of new dominant organisms and the stabilization of social hierarchies, which leads to individuals’ growth showing similar patterns, independent of their size (Barbosa et al [2006], Peacor et al [2007b]). Figure 1 illustrates the two stages of fish growth in accordance with these empirical findings.…”
Section: The Biological Modelsmentioning
confidence: 99%
“…A critical problem in the production of Nile tilapia Oreochromis niloticus in intensive and hyper-intensive systems (30-400 fish m -3 ) is the heterogeneity of body size. The organisms in the same cohort show different growth rates in response to biotic and abiotic factors (Barbosa et al, 2006;Azaza et al, 2013).…”
Section: Introductionmentioning
confidence: 99%